Mrs BODY, MIND, FUTURE: KESEHATAN REPRODUKSI SEBAGAI INVESTASI HIDUP PENCEGAHAN HIV/AIDS REMAJA - Wulan Novika Ambarsari; Afrieani Deasy; Ijun Rijwan Susanto; Keiko Pasaribu; Kania Permata Anggina; Anzas Junjun Bardiana; Riska Ayu Pratiwi; Rifa Awalani Agustin (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Adolescence is a period of transition marked by rapid physical, psychological, and social changes, requiring adolescents to have a proper understanding of reproductive health. In Indonesia, reproductive health literacy among adolescents is still low, increasing the risk of unwanted pregnancies, sexually transmitted infections, and anxiety related to bodily changes. The pre-test results at Handayani 1 Pameungpeuk High School showed that most students were in the low knowledge category. Therefore, a seminar entitled “Body, Mind, Future: Reproductive Health as an Investment in Life” was held to increase students' understanding and awareness. This study used a one-group pretest-posttest design with 90 respondents. The analysis was conducted using frequency distribution and percentages. The results showed a significant increase in knowledge, marked by an increase in the “Very Good” category from 5 to 24 students and a decrease in the low category. This seminar proved to be effective and is recommended to be implemented continuously in schools.